Analytical Investigation of the Applicability of Seismic Devices for Core Frames System in High-Rise Buildings - Dyah Kusumastuti; Muslinang Moestopo; Mega Suci Ramadhita; Erwin Lim; Randy Tanderan; Undagi Kausar Akbar (Institut Teknologi Sepuluh Nopember, 2017)
The use of link element in high rise buildings has been applied widely and proven to be effective in the eccentric braced frame system. Latest research has also shown that the applicability of link element can be extended to other type of structural systems, such as: coupled wall system or structures with core wall. The research showed that the use of link element could lead to better deformation capacity of the system and the link elements could act as a “fuse” to limit the input of earthquake force. However, the improvement of the seismic behavior may not be effective for any type of structural system. This paper investigates analytically parameters affecting the effectiveness of the application of shear link elements within a structural system. Several parameters being studied are the relative stiffness between link element and structural stiffness, types of structural configuration, etc.